Select medical holdings corp - private equity buyout - Ferraz, Catarina Rocha (2021)
The following Investment Committee Paper consists of a proposal fora Leveraged Buy out on Select Medical Holdings Corp, a United States key player, operating in different segments-Rehabilitation Hospitals, Out patient Rehabilitation Clinics, Occupational Health Centers, and Critical Illness Recovery Hospitals. In thi spaper, the group presents an investment the sis comprising of value creation strategies suchas portfolio expansion, operation al turnaround ,and strategic acquisitions that are incorporated in a forecasted operating model. After wards, a company valuation is conducted as well as an assessment of the optimal capital structure .Lastly, possible exit options are presented, and returns are calculated.